Enhancing transparency and accountability in public administration through information technology utilization - Sarifudin, Risman; Damanik, Fritz Hotman Syahmahita (Gema Wiralodra, 2024)
Many problems regarding the use of information technology to provide and increase transparency and accountability in public administration must be studied more deeply. Based on these problems, this study aims to explore and examine the use of information technology in increasing transparency and accountability in terms of public administration. The method used in this study is the qualitative research method.  Data Collection Techniques in this study go through three stages: observation, interviews, and search for supporting written data.  After the data is obtained, data analysis is carried out. Data analysis is carried out using qualitative analysis methods. The findings underscore that IT implementation significantly improves accessibility to public information, fosters a culture of efficiency through streamlined administrative practices, and strengthens oversight mechanisms. Moreover, the study identifies challenges related to data security, disparities in IT access, and resistance to technological change within administrative structures. Recognizing the necessity for comprehensive policies, the research emphasizes the need for governance frameworks that embrace technological advancements and address associated challenges. The study advocates for a holistic approach to maximize the positive impact of IT on transparency and accountability in public administration. This research contributes to the discourse on the intersection of technology and governance, providing insights that can inform policymakers, administrators, and researchers in advancing effective strategies for utilizing IT to foster transparency and accountability in public administration.